Tracking the visitor: An optical indoor system for visitor research in museums - Köferl, Franz; Jami, Jitin; Li, Jindong; Zanca, Dario; Eskofier, Björn; Zürl, Matthias (AI in Museums: Reflections, Perspectives and Applications, 2023)
The analysis of the success of any exhibition depends on the visitor experience. The data required for analysis is usually painstakingly collected by hand. We propose a large-scale optical tracking pipeline to estimate visitor data such as visit trajectory, duration, and, potentially, other personal parameters like age, weight, and sex, yet remain ethically acceptable by obtaining visitor consent. We further show, in preliminary results, that the edge device has a localization error of 0.64 meters and an average precision of 0.2. With this work-in-progress, we intend to ensure a viable alternative to current data collection processes in museum research.
CRIS-Team Scopus Importer:2024-12-16